Questioning the Mantra ‘All for One and One for All’: The Reintegration of Aceh’s Female Ex-combatants - Arifah Rahmawati (Revue Internationale de Politique de Développement)
The involvement of female combatants in the Aceh conflict challenges the stereotype of peaceful women, but these women have largely been overlooked in formal peacebuilding programmes. Using a qualitative approach, this chapter reveals the complex ways in which gender obstructs just and fair reintegration. Three areas are looked at closely: social reintegration (public acceptance of ex-combatants), economic reintegration (access to compensation) and political reintegration (support for female ex-combatants’ candidacy to the local parliament). The chapter finds that gender in intersection with other identities influences which female ex-combatants benefit from reintegration programmes. It explores explanatory factors such as loyalty to the struggle for freedom, the timing of disarmament, and kinship with male elites (men in power)—identifying the last of these as the most important. Although female ex-combatants do not face social stigma in this context, their access to economic and political reintegration benefits is limited and strongly influenced by their kinship with and proximity to men in power. Consequently, Aceh’s female ex-combatants cannot be seen as homogenous. Post-conflict peacebuilding programmes have created inequalities, and the old mantra ‘all for one, one for all’ has lost its meaning. These findings underscore the importance of looking at equality and inclusivity in an intersectional way at every stage of peacebuilding, including where reintegration processes are concerned.